2015
DOI: 10.1002/eji.201545798
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane TNF‐α is sufficient for articular inflammation and hypernociception in a mouse model of gout

Abstract: Gout manifests as recurrent episodes of acute joint inflammation and pain due to the deposition of monosodium urate (MSU) crystals within the affected tissue in a process dependent on NLRP3 inflammasome activation. The synthesis, activation, and release of IL-1β are crucial for MSU-induced inflammation. The current study evaluated the mechanism by which TNF-α contributed to MSU-induced inflammation. Male C57BL/6J or transgenic mice were used in this study and inflammation was induced by the injection of MSU cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 31 publications
(57 reference statements)
4
43
0
1
Order By: Relevance
“…The intra-articular injection of MSU crystals induces the onset of pain-like behavior in mice [10, 32]. In accordance with the findings of a previous study, the mechanical pain threshold of mice decreased obviously and allodynia was induced after an intra-articular ankle injection of MSU crystals; this effect reached a maximum 8 h after injection and lasted 72 h in our study.…”
Section: Discussionsupporting
confidence: 92%
“…The intra-articular injection of MSU crystals induces the onset of pain-like behavior in mice [10, 32]. In accordance with the findings of a previous study, the mechanical pain threshold of mice decreased obviously and allodynia was induced after an intra-articular ankle injection of MSU crystals; this effect reached a maximum 8 h after injection and lasted 72 h in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Although sTNFα is a major ligand for TNFR1, tmTNFα has been shown to induce inflammation and cytotoxicity through TNFR1 (Horiuchi et al, 2010). A recent study showed that tmTNFα was sufficient to cause inflammation in a gout model, and therefore, inhibition of sTNFα by XPro1595 did not provide beneficial effects (Amaral et al, 2016). Moreover, lymphotoxin (LTα3), formerly known as TNFβ, binds to both TNFRs (Tracey et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Leukocyte recruitment into the knee joint is a hallmark of gout inflammation and arthritis pathology [40,41]. Thus, based on previous results, we selected the most active doses (10μg) of IL-17Ab to test the modulation of leukocyte recruitment and activation.…”
Section: Il-17ab Ameliorates Msu-induced Leukocytes Recruitment and Amentioning
confidence: 99%
“…All these processes are mainly related to activated neutrophils and macrophages which are responsible for the release of PGE2, IL-1β, TNF-α, and, activate nociceptor neuron and thereby producing pain [53,54,55]. Indeed, targeting IL-1β, TNF-α or PGE2 in rheumatic diseases reduce neutrophil recruitment and associated pain [40].…”
Section: A C C E P T E Dmentioning
confidence: 99%